Vision Deficits in Adults with Down Syndrome. Issue 3 (19th June 2013) - Krinsky‐McHale, Sharon J.; Silverman, Wayne; Gordon, James; Devenny, Darlynne A.; Oley, Nancy; Abramov, Israel
<x xml:space="preserve">Abstract</x> Background In individuals with Down syndrome, virtually all structures of the eye have some abnormality, which likely diminishes vision. We examined basic vision functions in adults with Down syndrome. Materials and Methods Participants completed a battery of psychophysical tests that probed a comprehensive array of visual functions. The performance of adults with Down syndrome was compared with younger and older adults without intellectual disability. Results Adults with Down syndrome had significant vision deficits, reduced sensitivity across spatial frequencies and temporal modulation rates, reduced stereopsis, impaired vernier acuity and anomalies in colour discrimination. The pattern of deficits observed was similar to those seen by researchers examining adults with Alzheimer's disease. Conclusions Our findings suggest that a common mechanism may be responsible for the pattern of deficits observed, possibly the presence of Alzheimer's disease neuropathology in the visual association cortex. We also showed that individuals with mild to moderate intellectual disability are capable of participating in studies employing state‐of‐the‐art psychophysical procedures. This has wider implications in terms of their ability to participate in research that use similar techniques.